PENGENDALIAN PENCEMARAN LINGKUNGAN DENGAN PENERAPAN TEKNOLOGI PROSES TERBAIK Ã¢â‚¬Å“BEST AVAILABLE TECHNIQUESÃ¢â‚¬Â UNTUK PRODUKSI AMONIAK - Wiwoho, Djoko (Jurnal Teknologi Lingkungan, 2000)
Best Available Techniques (BAT) is developed especially in the European Community, responding environmental issue by designing the process that the polluted chemicals released during the plant operation are still under the environmental tolerances. Beside environmentally friendly, the technology is also efficient and consumes less energy.